Pengaruh Islamic Branding, Price Fairness, dan Service Quality Terhadap Loyalitas Pelanggan Yang Dimediasi Oleh Customer Satisfaction (Studi Pelanggan Elisha Mart Ngaliyan) - Ramadhanti, Desta Fitri; Cahyono, Edi (Cattleya Darmaya Fortuna, 2024)
This research aims to determine the influence of Islamic Branding, Price Fairness and Service Quality on Customer Loyalty Mediated by Customer Satisfaction among Elisha Mart Ngaliyan customers. This research is quantitative research with primary data, data collection was carried out by distributing questionnaires to 206 people from Elisha Mart Ngaliyan customers. The sampling method and technique used 200. And the data analysis tool used was IBM SPSS Statistics 29 software. Based on the t test results, it showed that Islamic branding and price fairness had a positive and significant effect on customer loyalty. Meanwhile, serice quality has no effect on customer loyalty. Then, Islamic branding, price fairness, service quality have a positive and significant effect on customer satisfaction. Based on path analysis, it shows that customer satisfaction has a significant positive effect on mediating price fairness on customer loyalty but is unable to mediate between Islamic branding and service quality on customer loyalty. This research can be used as consideration for Elisha Mart in improving and increasing customer satisfaction as needed.